Undang-undang dan pengurusan alam sekitar menurut Islam - Abdul Basir Mohamad, (Environmental Management Society, Malaysia, 2005)
Human being’s natural inclination is not contrary to Islam, and Islamic principles are not contrary to human beings’ natural feeling and needs too. Things that are offensive to Islam are also not wanted by human. In the protection of the environment, what is required by Islam is in line with human beings’ need and tastes. However, human beings’ greed leads to disregard of the environment, and they may do anything possible so long as their greedy desires can be satisfied. They may also act against those who enforce laws, and those who exposed cases related to the violation of environmental laws and regulations. If the adverse intrusion into the environment is against the wills of the local communities and environmentalists, it is also against Islam. This paper looks into the environmental management laws and regulations from Islamic perspective